Effects of different algal diets on the settlement, growth, and survival of green mussel Perna viridis Pediveliger - Maquirang, Jean Rose H. (Miag-ao, Iloilo University of the Philippines Visayas, 2018)
Three species of tropical microalgae were investigated t determine their efficacy as settlement inducer and feed for green mussel (Perna vridis) larvae, Pediveliger larvae (2 larvae ml-1) were given monoalgal diets such as golden brown flagellate Isochrysis galbana (Iso), diatom Chaetoceros calcitranz (Cc), and green alga Tetraselmis tetrahele (Tt) at a feeding ration of 100,000 cells mL-1 (1:2.5:0.1 cell volume basis, respectively). Settlement assay was done in 90mm petri dish plates and assessed every 2, 4 and 6 days. An unfed treatment which served as negative control was also included in the assay. percent settlementwere both high on the different microalgae tested during days 4 and 6 but not significantly different from th control (p>0.05). Survival was high on larvae fed Iso but not significantly different from the Cc and Tt fed larvae. Compared to other diets, Ccpromoted maximu growth in terms of final shell height (SH) and shell length measurements (SL) as well as instantaneous growth rate (k). Ingestion rate was significantly high in the Cc and Iso-fed larvae, compared to the larvae fed with Tt. Furthermore, all diets are readily ingested and digested by larvae based on epiflourescence microscopy. Digestion of cells by the larvae was faster i Cc followed by Iso, then Tt algae. The results indicated that Iso and Cc promote good larval performance and therefore recommended as appropriate diets for the green mussel pediveliger larvae. Findings on the various algal densities of each microalgae revealed an appropriate cell density of 20 cell uL-1, 200 cells uL-1, and 150 uL-1 for T. tetrahele, I. galbana, and C. calcitrans, respectively, due to the high ingestion rate activity of the larvae.
Thesis (M.S. Fisheries-Aquaculture) -- Miagao, Iloilo : U. P. Visayas, July 2018.